PEMBELAJARAN DENGAN MODEL INKUIRI PADA MATERI KIMIA SEKOLAH MENENGAH ATAS - Rachmat Sahputra (STKIP Melawi, 2014)
Abstract: Learning with the inquiry model inchemistry material in high school has not been practiced in the learning process to the fullest, and this study aims to determine the chemical understanding of high school students using inquiry learning model. The method use disdescriptive qualitative approach. The sampling technique was used purposive sampling with data collection tool used to measure students' understanding of chemistry is the achievement test and lab worksheets. Understanding the chemical being measured include chemical content, process chemistry, and chemical context. Achievement test used to measure the chemical content and context, while the lab worksheets are used to measure the chemical process. Based on the analysis of the data obtain edit can be concluded that the category of high school students' understanding of chemistry can bein creased through inquiry learning model with the percentage reached 82.1% of students in a class of chemical understand well enough, although still in the moderate category.Keywords: chemistry understanding, inquiry model.Abstrak: Pembelajaran dengan model inkuiri pada materi kimia di SMA belum dipraktikan dalam proses pembelajaran secara maksimal, dan penelitian ini bertujuan untuk mengetahui pemahaman kimia siswa SMA menggunakan model pembelajaran inkuiri. Metode penelitian yang digunakan adalah deskriptif dengan pendekatan kualitatif. Teknik pengambilan sampel yang digunakan adalah purposive sampling dengan alat pengumpul data yang digunakan untuk mengukur pemahaman kimia siswa adalah tes hasil belajar dan LKS praktikum. Pemahaman kimia yang diukur meliputi konten kimia, proses kimia, dan konteks kimia. Tes hasil belajar digunakan untuk mengukur konten dan konteks kimia, sedangkan LKS praktikum digunakan untuk mengukur proses kimia. Berdasarkan analisis data yang diperoleh dapat disimpulkan bahwa kategori pemahaman kimia siswa SMA dapat meningkat melalui model pembelajaran inkuiri dengan persentase mencapai sebesar 82,1% siswa dalam kelas cukup memahami kimia dengan baik, meskipun masih dalam kategori sedang.Kata kunci: pemahaman kimia, model inkuiri.